Post-Dural Puncture Headache is Uncommon in Young Ambulatory Surgery Patients. Issue 2 (July 2017) - DelPizzo, Kathryn; Cheng, Jennifer; Dong, Naomi; Edmonds, Chris R.; Kahn, Richard L.; Fields, Kara G.; Curren, Jodie; Rotundo, Valeria; Zayas, Victor M.
Background: The incidence of post-dural puncture headache (PDPH) arising from spinal anesthesia in the general population is low. However, patients under 45 years have been shown to exhibit a higher incidence of PDPH, even with small needles. Questions/Purposes: This study aimed to estimate the incidence of PDPH from a 27G pencil-point needle in ambulatory surgery patients between the ages of 15–45 years and compare incidence of PDPH by age group, sex, and history of headache. Methods: In this prospective cohort study, 300 patients (15–45 years old) who underwent simple knee arthroscopy under spinal anesthesia with a 27G pencil-point needle were enrolled. Verbal consent was obtained during the initial phone conversation between post-operative days (PODs) 2–5. A PDPH questionnaire was administered during this conversation and between PODs 7–10. Patients who reported a positional headache were contacted by a physician co-investigator, who determined PDPH diagnosis. Results: Five patients were excluded from analysis due to complicated operative procedures or spinal needle size. The overall PDPH incidence was 2.0% (95% CI 0.9–4.4; 6/295). PDPH incidence in 15–19-year-old patients was 16.7% (95% CI 4.7–44.8; 2/12). The crude relative risk of PDPH was 15.4 (95% CI 2.8–114.4) for patients with and without history of headache and 2.5 (95% CI 0.5–14.8) for females vs. males. Overall, 16.3% (95% CI 12.5–20.9) of patients reported post-operative, non-positional headaches. Conclusions: There was a low overall incidence of PDPH among patients aged 15–45. Pre-planned subgroup analyses of PDPH incidence by age group revealed a high risk of PDPH among a small sample of 15–19-year-olds.